Comprehensive Biological and Chemical Evaluation of Two Seseli Species (S. gummiferum and S. transcaucasicum) - Gokhan Zengin; Dejan Stojković; Mohamad Fawzi Mahomoodally; Bibi Sharmeen Jugreet; Mehmet Yavuz Paksoy; Marija Ivanov; Uroš Gašić; Monica Gallo; Domenico Montesano (MDPI AG, 2021)
Seseli L. is one of the largest genera of the Apiaceae family widely known for their traditional uses as herbal remedies. In the present study, the methanolic and water extracts of two Seseli species, S. gummiferum and S. transcaucasicum were evaluated for their bioactive contents and biological activities. The total phenolic and flavonoid contents in the extracts ranged from 19.09 to 24.33 mg GAE/g and from 0.45 to10.09 mg RE/g, respectively. Moreover, while narcissin was detected as the most abundant component in the methanolic extract of S. transcaucasicum (261.40 µg/g), chlorogenic acid was identified as the major component in all the other extracts, although a high amount was also present in the methanolic S. transcaucasicum extract (107.48-243.12 µg/g). The total antioxidant capacity was also determined by the phosphomolybdenum assay (0.66-1.18 mM TE/g). Other antioxidant assays such as the radical scavenging assays (DPPH: 5.51-11.45 mg TE/g; ABTS: 43.46-51.91 mg TE/g), reducing assays (CUPRAC: 41.67-53.20 mg TE/g; FRAP: 31.26-34.14 mg TE/g), as well as the metal chelating activity assay (14.38-38.57 mg EDTAE/g) were conducted. All the extracts showed inhibitory potential against the enzyme's amylase (0.12-0.78 mM ACAE/g), acetyl- and butyryl-cholinesterase (0.15-9.71 mg GALAE/g), while only the methanolic extracts acted as inhibitors of tyrosinase (107.15 and 109.37 mg KAE/g) and only the water extract of S. gummiferum displayed anti-glucosidase activity (0.13 mM ACAE/g). Interestingly, the methanolic extracts of both Seseli species showed lower cytotoxicity towards HaCaT cells (IC50: >500 µg/mL), compared to the water extracts (IC50: 267.8 and 321.41 µg/mL). Besides, only the methanolic extracts showed a slight wound healing effect (28.21 and 31.23%). All extracts showed antibacterial action against Staphylococcus lugdunensis (minimum inhibitory and bactericidal concentrations: 0.025-2 mg/mL). S. gummiferum methanolic extract, which exhibited the highest antibacterial potency was found to inhibit adhesion and invasion of S. lugdunensis to HaCaT cells as well. Taken together, this study demonstrated the two Seseli species to harbour interesting bioactive components, in particular polyphenolics and to exhibit several biological properties that could be further investigated for their potential exploitation as healing agents as supported by various traditional medicinal uses.